1999
DOI: 10.1007/s100530050453
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of Li@C60

Abstract: The thermal stability of purified endohedral Li@C 60 has been studied. There are two endohedral compounds produced from Li + irradiated C 60 that have slightly different stabilities. The endohedral species decay at elevated temperatures on a time scale of a few hours when in solution and exposed to light and air. The dry, purified material has a higher thermal stability and can be sublimed in vacuum to produce thin films of pure endohedral fullerenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This yields an activation energy for the cage destruction within the oven of 1.27±0.05 eV (errors are the 95% confidence limits from the straight line fit). This value is remarkably close to the activation energy determined previously for Li loss from the dimerised endohedral species in solution (1.1 ± 0.2 eV) [15]. It is much lower that the value of 5.4±0.2 eV obtained for release of Li from the isolated gas phase cationic endohedral molecules that is similar to the threshold energy for Li + implantation in C 60 [16] and the bias voltage at which Li loss from the C 60 cage is observed in STM experiments [9].…”
Section: Methodssupporting
confidence: 90%
“…This yields an activation energy for the cage destruction within the oven of 1.27±0.05 eV (errors are the 95% confidence limits from the straight line fit). This value is remarkably close to the activation energy determined previously for Li loss from the dimerised endohedral species in solution (1.1 ± 0.2 eV) [15]. It is much lower that the value of 5.4±0.2 eV obtained for release of Li from the isolated gas phase cationic endohedral molecules that is similar to the threshold energy for Li + implantation in C 60 [16] and the bias voltage at which Li loss from the C 60 cage is observed in STM experiments [9].…”
Section: Methodssupporting
confidence: 90%
“…This finding does not contradict the LD TOF MS results, which show for both fractions pronounced peaks at 727 u, corresponding to monomeric LiC 60 . It has been shown that isolated endohedral Li@C 60 species possess limited thermal stability, and they undergo complete dissociation of the interfullerene bonds under the rather extreme LD MS conditions. The same problem occurs for other dimeric species, for example, (C 60 ) 2 42 and (C 70 ) 2 …”
Section: Resultsmentioning
confidence: 99%
“…The production and isolation of Li@C 60 from unreacted C 60 and other byproducts have been described elsewhere. , The fullerene film after low-energy ion bombardment was washed from the substrate by carbon disulfide (CS 2 ) in an ultrasonic bath. The CS 2 -soluble part was examined by HPLC using a Cosmosil 5PBB column (Nacalai Tesque), 10 mm i.d., 25 cm length, and 1,2-dichlorobenzene as eluent at a flow rate of 2.5 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…tended to polymerize within the C 60 matrix so that the product was difficult to be extracted with common organic solvents. 91 Recently, an improved ion implantation method was reported jointly by several Japanese groups. 35 They used Li + plasma to attack the C 60 -films deposited on a metal plate.…”
Section: Ion Implantationmentioning
confidence: 99%